Analysis of the Influence of Profitability, Leverage and ESG Disclosure on the Value of Sharia Stock Companies Registered on the ESGL Index - Hadi, Ibrahim; Kaban, Reny Fitriana (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This research aims to analyze the significance of the influence of profitability, leverage, and ESG Disclosure on company value. Return On Assets is an indicator of profitability, Debt to Equity Ratio is an indicator of leverage, ESG Score by Sustainilytics is an indicator of ESG Disclosure and Price to Book Value is an indicator of company value. The method used in the research is descriptive and quantitative. This research sample used a purposive sampling technique with 17 Sharia stock companies listed on the ESG index. The data analysis used in this research is panel data regression. The statistical test results show that profitability has a significant influence on company value. The leverage variable shows a significant effect on company value. Meanwhile, the ESG Disclosure variable has no influence on company value. This is related to company value. Companies listed on the ESGL index are expected to be consistent in improving their performance in order to increase profitability and leverage and remain consistent in implementing the concept of governance and social sustainability towards company value. The higher the profitability and leverage, the higher the company value. The higher the ESG score the company has, the better the company implements the concept of sustainability.